2017
DOI: 10.1007/s00239-017-9820-x
|View full text |Cite
|
Sign up to set email alerts
|

Putative Independent Evolutionary Reversals from Genotypic to Temperature-Dependent Sex Determination are Associated with Accelerated Evolution of Sex-Determining Genes in Turtles

Abstract: The evolutionary lability of sex-determining mechanisms across the tree of life is well recognized, yet the extent of molecular changes that accompany these repeated transitions remain obscure. Most turtles retain the ancestral temperature-dependent sex determination (TSD) from which multiple transitions to genotypic sex determination (GSD) occurred independently, and two contrasting hypotheses posit the existence or absence of reversals back to TSD. Here we examined the molecular evolution of the coding regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Nonetheless, compared to T. scripta, our data from stage 15 C. picta suggest that Dmrt1 is unlikely to sit at the top of the male determination cascade in painted turtles, although further research is warranted, particularly in light of the thermosensitive response of the ratio of the canonical transcript to Dmrt1 Ex2Ex3 at stage 15. Additional differences in the timing of expression among taxa provide evidence of a divergent regulation of Dmrt1 across vertebrates irrespective of the mode of sex determination (TSD or GSD), unlike Dmrt1's molecular evolution, which appears linked to transitions between TSD and GSD in terms of the rate at which sequences evolve (Literman et al, 2018) and in terms of shifts in the sequence of amino acids (Janes et al, 2014). Why exactly does Dmrt1 vary in the number of isoforms that are produced in different taxa remains an open question.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, compared to T. scripta, our data from stage 15 C. picta suggest that Dmrt1 is unlikely to sit at the top of the male determination cascade in painted turtles, although further research is warranted, particularly in light of the thermosensitive response of the ratio of the canonical transcript to Dmrt1 Ex2Ex3 at stage 15. Additional differences in the timing of expression among taxa provide evidence of a divergent regulation of Dmrt1 across vertebrates irrespective of the mode of sex determination (TSD or GSD), unlike Dmrt1's molecular evolution, which appears linked to transitions between TSD and GSD in terms of the rate at which sequences evolve (Literman et al, 2018) and in terms of shifts in the sequence of amino acids (Janes et al, 2014). Why exactly does Dmrt1 vary in the number of isoforms that are produced in different taxa remains an open question.…”
Section: Resultsmentioning
confidence: 99%
“…Most turtles possess TSD, a system that appears ancestral to turtles, reptiles, and likely to all amniotes based on the most complete phylogenetic comparative analyses possible to date given the existing information [15,[19][20][21]. These species-level phylogenetic analyses revealed that the history of turtle sex determination is marked by the retention of an ancestral TSD mechanism in most chelonian lineages, punctuated by few transitions to sex chromosomes (five so far identified), and two potential reversals from GSD back to TSD where sex chromosomes may have been lost [19,22] (Figure 1). Phylogenetic relationships of turtles with a known sex-determining mechanism (SDM) and diploid number (2N).…”
Section: Sex Chromosomes Were Gained and Lost Multiple Times In Turtlesmentioning
confidence: 99%
“…However, these reversals are questionable given that their inference is not parsimonious [20], and that reanalysis of the same dataset by maximum likelihood reconstruction of ancestral SDMs using an updated software package did not recover the same result [21]. Yet, the significant intensification of the rate of molecular evolution of sexual development genes observed in both Carettochelyidae and Podocnemididae [22], above and beyond the already accelerated rate seen in their GSD sister lineages, supports the notion that GSD-to-TSD reversals might have taken place. Moreover, the branching of these lineages suggests that these reversals might have occurred soon after GSD evolved in the common ancestor of Carettochelyidae and Trionychidae, and in the common ancestor of Podocnemididae and Chelidae, likely before extensive differentiation of their sex chromosomes accrued that would have been harder to overcome [1,15].…”
Section: Sex Chromosomes Were Gained and Lost Multiple Times In Turtlesmentioning
confidence: 99%
See 1 more Smart Citation
“…And mun-novel31-3p could target RNF2 (associated with regulation of genetic imprinting ( Li, Zhang & Wu, 2017 )). mun-novel68-3p might regulate HSF2 which related to sex-determining ( Literman et al, 2018 ), mun-miR-2954-3p and mun-novel72-3p could target KITLG (sex development) ( Hersmus et al, 2017 ) ( Table S4 ). Of all the miRNAs tested, we found three gonad-enriched miRNAs (mun-miR-215-5p, mun-novel10-5p and mun-novel24-3p).…”
Section: Discussionmentioning
confidence: 99%